2018
DOI: 10.1007/s11548-018-1848-x
|View full text |Cite
|
Sign up to set email alerts
|

Semiautomatic neck curve reconstruction for intracranial aneurysm rupture risk assessment based on morphological parameters

Abstract: The new 3D neck curve reconstruction provides robust results for all datasets. The reproducibility depends on the vessel tree centerline and the user input for the initial dome point and parameters characterizing the aneurysm neck region. The characteristic dome point angle as a new metric regarding rupture risk assessment can be extracted. It requires less computational effort than the complete neck curve reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…2) During the analysis of clinically relevant morphological and hemodynamic parameters, it was found that these parameters are highly sensitive to the choice of the aneurysm ostium and neck curve, respectively. Therefore, a realistic separation of aneurysm and parent vessel is recommended when quantification of shape and flow parameters is carried out, e.g., using objective algorithms [3436]. This is particularly required to avoid uncertainties due to subjective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2) During the analysis of clinically relevant morphological and hemodynamic parameters, it was found that these parameters are highly sensitive to the choice of the aneurysm ostium and neck curve, respectively. Therefore, a realistic separation of aneurysm and parent vessel is recommended when quantification of shape and flow parameters is carried out, e.g., using objective algorithms [3436]. This is particularly required to avoid uncertainties due to subjective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these points, a neck curve was created and the ostium plane derived. For a detailed description of the computational process, see Saalfeld et al [ 29 ]. Utilizing the neck curve and ostium plane, the following morphological parameters were automatically extracted: aneurysm surface area (A), aneurysm volume (V), ostium area1 (OA1), ostium area2 (OA2), maximum diameter (Dmax), maximum height (Hmax), maximum width perpendicular to Hmax (Wmax), maximum height perpendicular to the ostium plane (Hortho), maximum width parallel to the ostium plane (Wortho), maximum neck curve diameter (Nmax), average neck curve diameter (Navg), aspect ratio 1 (AR1), aspect ratio 2 (AR2), volume of the convex hull (Vch), surface area of the convex hull (Ach), ellipticity index (EI), non-sphericity index (NSI), undulation index (UI), and aneurysm tilt angle γ [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of geometric parameters requires the separation of the aneurysm head from the parent vessel, which was done manually by one operator for all data sets. Although a small inter-operator dependency analysis found minor impact on the calculation of geometric parameters [31], this procedure could be replaced by an automated approach in the future [17].…”
Section: Discussionmentioning
confidence: 99%
“…To provide a clinically applicable workflow, Saalfeld et al [17] analysed 100 IAs by means of a semi-automatic neck curve reconstruction algorithm. The authors identified the characteristic dome point angle as a potential morphologic candidate to assess rupture risk.…”
Section: Introductionmentioning
confidence: 99%